Gangland : this unsporting life - Morton, James, 1938-; Lobez, Susanna (Victory Books, 2019)
Sport has always attracted organised crime. Huge sums of money are wagered in every arena, and rorts, swindles and unsporting behaviour have shadowed players of all codes. Cricket and footy are not immune, with Heath Shaw and Ben Cousins caught up in gambling and drugs, and NRL star Ryan Tandy in match-fixing. Drugs play a major part on and off the fields of play (looking at you, Essendon Football Club and Cronulla-Sutherland Sharks) with horses and greyhounds also routinely doped. James Morton and Susanna Lobez investigate the cheating underbelly of sport, from the first cricket pitch invasion in the 1890s through to the contemporary scandals that will leave you wondering if there is such a thing as a sporting chance.